ICT-based fluorescent probes for intracellular pH and biological species detection - Wu, You; Ge, Chengyan; Zhang, Ying; Wang, Yalong; Zhang, Deteng (Frontiers in Chemistry, 2023)
Fluorescent probes, typically based on the intramolecular charge transfer (ICT) mechanism, have received considerable research attention in cell detection because of their non-invasive, fast response, easy regulation, high sensitivity, and low damage for in vivo bio-samples. Generally, intracellular PH and biological species such as various gases, metal ions as well as anions constitute the foundation of cells and participate in the basic physiological processes, whose abnormal level can lead to poisoning, cardiovascular disease, cancer etc. in living organisms. Therefore, monitoring of their quantity plays essential role in understanding the status of organisms, and preventing, diagnosing and treating diseases. In the last decades, remarkable progress has been made in developing ICT probes for biological elements detection. In this review, we highlight the recent ICT probes focusing primarily on detection of intracellular PH, various gases (H2S, CO, H2O2, and NO), metal ions (Cu2+, Hg2+, Pb2+, Zn2+ and Al3+) and anions (ClO-, CN-, SO32- and F-). In addition, we discussed the issues and limitations of ICT-based fluorescence probes for in vivo detection, and explored the clinical translational potential and challenges of these materials, providing valuable guidance and insights for the design of fluorescence materials.